Emerging Biomarkers and Electrochemical Biosensors for Early Detection of Premature Coronary Artery Disease - Nanthini Mageswaran; Sarah Husnaini Zainal; Nurul Izzaty Hassan; Nurul Huda Abd Karim; Noor Akmal Shareela Ismail (Diagnostics)
Coronary artery disease (CAD) is one of the primary causes of morbidity and death worldwide. Premature CAD (pCAD) is the term used to describe the 3–10% of CAD occurrences that occur in people under 45 worldwide. Diagnostic difficulties arise from the different risk factor profiles of pCAD and late-onset CAD. Better cardiovascular risk prediction in younger populations has been made possible by the development of biomarker detection tools. This can be applied to a diagnostic tool, including electrochemical biosensors, which have been predicted to be instrumental because of their adaptability for point-of-care applications for quicker diagnoses. These biosensors provide efficient, scalable, and reasonably priced solutions for the quick identification and tracking of CAD. Multiplex biomarker detection has been adopted as a viable approach for early diagnosis and risk assessment due to the constraints of using a single biomarker for pCAD diagnosis. Thus, this study looks at current developments in biosensing technology and discusses established and new cardiac biomarker panels for pCAD identification.